Policing Repeat and High-Risk Family Violence: A Coordinated Model in Victoria, Australia - Hamilton, Gemma (Kriminalističke teme, 2018)
This study qualitatively evaluated ‘Alexis – Family Violence Response Model’— a joint police-social services approach to family violence in the State of Victoria (Australia). Interviews were conducted with 17 stakeholders (7 police members and 10 community service providers) to examine how the model reduced recidivist family violence and how it differed from other policing approaches to family violence. Five key themes were extracted from the data via thematic analysis: (i) collaboration between police, an embedded family violence worker and other agencies; (ii) increased police accountability; (iii) the adoption of a proactive major crime approach; (iv) emphasis on professional development; and (v) the allocation of dedicated time and resources. Implications for future policy development are discussed, with the findings highlighting promising practices for policing high-risk and recidivist family violence.